Advances in Ovarian Cancer Care and Unmet Treatment Needs for Patients With Platinum Resistance: A Narrative Review - Richardson, Debra L; Eskander, Ramez N; O'Malley, David M (JAMA oncology, 2023)
Platinum-based chemotherapy has been the standard of care for ovarian cancer for the past 3 decades. Although most patients respond to platinum-based treatment, emergence of platinum resistance in recurrent ovarian cancer is inevitable during the disease course. Outcomes for patients with platinum-resistant ovarian cancer are poor, and options remain limited, highlighting a substantial unmet need for new treatment options. This review summarizes the current and evolving treatment landscape for platinum-resistant ovarian cancer with a focus on the development of novel compounds. Biologic and targeted therapies such as bevacizumab and poly (ADP-ribose) polymerase (PARP) inhibitors-originally approved in the platinum-resistant setting but since withdrawn-are now used in the up-front or platinum-sensitive setting, prolonging the duration of platinum sensitivity and delaying the use of nonplatinum options. The greater use of maintenance therapy and the emphasis on using platinum beyond first-line treatment has most likely been associated with a greater number of lines of platinum therapy before a patient is designated as having platinum-resistant ovarian cancer. In this contemporary setting, recent trials in platinum-resistant ovarian cancer have mostly had negative outcomes, with none having a clinically significant effect on progression-free or overall survival since the approval of bevacizumab in combination with chemotherapy. Nonetheless, a multitude of new therapies are under evaluation; preliminary results are encouraging. A focus on biomarker-directed treatment and patient selection may provide greater success in identifying novel therapies for treating platinum-resistant ovarian cancer. Although many clinical trials in platinum-resistant ovarian cancer have had negative outcomes, these failures provide insights into how clinical trial design, biomarker-directed therapy, and patient selection could facilitate future successes in platinum-resistant ovarian cancer treatment.